AJO “YANG POLITIS”: MENGGUGAT REZIM PARTISI DALAM CERPEN ROBOHNYA SURAU KAMI KARYA A.A. NAVIS - Yudhistira Nasution, Ricky (Adabiyyāt: Jurnal Bahasa dan Sastra, 2021)
This study aims to examine partitions and political actions in A.A. Navis’s short story “Robohnya Surau Kami” using Jacques Rancière’s concept of the distribution of the sensible theory. The method used in this study is qualitative descriptive research. It is important to recognize the awareness of the subject as part of the social class. This social class becomes the agent for various imaginary subjects constructed through discourse. The story indicates that there are characters who have been partitioned through the practice of polis and thus making them experience inequalities and restrictions. To escape from these, they need to carry out a political action (disensus; declassification; migration). The results showed that the Grandfather as protagonist was partitioned in the social structure based on his identity as a clergyman. This identity was used as a legitimizing sensibility to partition Grandfather as a “the part that has no part”. The partition that happened to him fits the Archipolitic and Parapolitic concepts. Meanwhile, the dissensus action aimed at declassifying was carried out by Ajo Sidi who created an allegory for Grandfather. In this allegory, Ajo presents a figure of God who challenges the partition regime as dissensus and subjectivating the figure of Haji Saleh/Grandfather as declassification. Based on this, Ajo Sidi can be said to be “the political” subject.